Preparation method and application of micron-hole TPU / rGO / carbon felt composite material
Through the composite material of TPU and rGO and carbon felt, a microporous structure is formed, which solves the structural instability and high cost of carbon felt materials in sensing applications, and achieves excellent flexible sensing performance and electromagnetic shielding performance. With versatility.
Patent Information
- Application Number
- CN202411265440.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-01-03
AI Technical Summary
Carbon felt materials have structural instability and high production costs in sensing applications, making it difficult to achieve excellent flexible sensing performance and electromagnetic shielding performance.
By combining TPU with rGO and carbon felt, a microporous structure was formed, and a porous structure was constructed by using TPU phase separation under a non-solvent system. On this basis, rGO was added to build a multi-dimensional conductive network to prepare a good flexible transmission with excellent Composite materials with inductive properties and electromagnetic shielding properties.
It improves the sensing stability and electromagnetic shielding performance of carbon felt materials, reduces production costs, and realizes versatility such as electric heating and flame alarm functions.
Smart Images

Figure CN119243484A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micron porous structures and flexible sensing materials, and specifically relates to a preparation method of a micron porous TPU / rGO / carbon felt composite material and application thereof. Background Art
[0002] Flexible sensing materials are materials that can maintain electrical conductivity when bent or stretched. Flexible sensing materials have received considerable attention in various academic and industrial fields. Although carbon felt materials have good electrical conductivity, the production of flexible sensors based on carbon felt faces huge challenges. Due to the loose structure of carbon felt materials, after a certain pressure is applied to its surface, it cannot return to its initial state, and the fluctuations are relatively large, resulting in unstable sensing performance. Therefore, pure carbon felt materials are not suitable for sensing. Patent CN 201811327703 describes a wavy carbon felt electromagnetic shielding structure and a preparation method thereof, characterized in that: the structure adopts multiple layers of wavy carbon felt combined at a certain angle, the wavy carbon felt uses resin as the matrix, and the carbon fiber felt is the functional body. Although this scheme can achieve excellent electromagnetic shielding performance, the following problems still exist: the single function, structure and production cost of the material are worrying.
[0003] TPU is a polymer elastomeric material with excellent mechanical properties and good biological properties. In a system with water as a non-solvent, TPU will form an irregular porous structure membrane. Combining this property of TPU with carbon felt materials greatly improves the sensing stability of carbon felt materials and also strengthens their mechanical properties. How to develop a method for preparing a carbon felt composite material with excellent flexible sensing performance and electromagnetic shielding properties based on the characteristics of TPU is a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a preparation method of a microporous TPU / rGO / carbon felt composite material and its application to solve the above-mentioned technical problems existing in the prior art.
[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing a microporous TPU / rGO / carbon felt composite material, specifically comprising the following steps: Step 1, preparation of rGO / carbon felt: Prepare a GO solution with a concentration of 5 mg / mL; select a GO solution with a unit area mass of 53 g·m −2The carbon felt was cut into 10 * 10 cm squares, immersed in acetone, and then placed in deionized water, washed several times, and placed in a 60 ° C oven to dry. Then the sample was immersed in a 5 mg / mL GO solution, taken out, and placed in a 60 ° C oven to dry for 1 hour. The above "immersion-drying" steps were repeated 10 times. Subsequently, the prepared sample was placed in HI (hydriodic acid) solution, and the GO on the surface of the carbon felt was in situ reduced to rGO at a temperature of 98 ° C to obtain an rGO / carbon felt composite material; Step 2: Preparation of microporous TPU / rGO / carbon felt: DMF (dimethylformamide) is selected as the solvent of TPU, and TPU and DMF are mixed in a certain weight ratio to form a uniform bubble-free TPU solution, and the TPU solution is dripped into a culture dish. The sample prepared in step 1 is placed in the culture dish, and the TPU solution is coated on both sides of the sample, and then placed in a room temperature environment to dry. During the drying process, due to the presence of water molecules in the air, TPU rapidly separates after encountering water, causing the surface of TPU to shrink severely, thereby causing the condensation of the DMF solvent phase, so that thumb-shaped and droplet-shaped uneven micron pores are formed on the surface of the sample.
[0006] Furthermore, preferably, the mass per unit area is selected to be 53 g·m −2 Carbon felt is used as the substrate.
[0007] Further, preferably, the carbon felt is immersed in a 5 mg / mL GO solution, taken out, placed in an oven at 60°C for 1 hour, and the above "immersion-drying" step is repeated 10 times to ensure that GO is evenly coated on the surface of the carbon felt fabric. Subsequently, the prepared pattern is placed in a HI (hydriodic acid) solution, and the GO on the surface of the carbon felt is in situ reduced to rGO at a temperature of 98°C, and then placed in an oven for drying to obtain an rGO / carbon felt composite material.
[0008] Furthermore, DMF (dimethylformamide) is selected as the solvent of TPU, and TPU and DMF are mixed in a certain weight ratio to form a uniform bubble-free TPU solution.
[0009] Furthermore, the TPU solution was dripped into a culture dish (a 1-5 mm solution layer was formed at the bottom), and the sample prepared in step 1 was placed in the culture dish so that both sides of the sample were coated with the TPU solution, and then placed in a room temperature environment to dry. During the drying process, due to the presence of water molecules in the air, the TPU rapidly separated into phases after encountering water, causing the surface of the TPU to shrink severely, thereby causing the DMF solvent phase to condense, so that thumb-shaped and droplet-shaped uneven micron pores were formed on the surface of the sample; the particle size range can be controlled by adjusting the mass ratio of TPU to DMF, and the particle size range is 8-50 μm.
[0010] Furthermore, by using carbon felt as a substrate, the structure of the nonwoven fabric is changed through a simple and quick method to form a porous structure, and to give it electromagnetic shielding properties, electric heating properties, sensing capabilities, flame alarms, etc.
[0011] Compared with the prior art, the present invention has the following advantages: (1) Based on the phase separation of TPU in a water-based non-solvent system, a porous structure is formed. This structure is combined with carbon felt material, and rGO is added to construct a multidimensional conductive network. The composite material has high scientific significance and practical value, and has guiding significance for improving the flexible sensing performance and electromagnetic shielding performance of carbon felt materials; (2) This method is simple and easy to operate, has low equipment requirements, is highly feasible, and has wide application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a physical picture of the sensing material of Example 1 of the present invention.
[0013] Figure 2 This is a microstructure diagram of the sensing material of Example 1 of the present invention (10 μm size).
[0014] Figure 3 This is a microstructure diagram of the sensing material of Example 1 of the present invention (20μm size).
[0015] Figure 4 This is a diagram of the resistance data caused by the pulse according to the first embodiment of the present invention.
[0016] Figure 5 This is a diagram of electromagnetic shielding data of the sensing material according to the first embodiment of the present invention.
[0017] Figure 6 This is a data diagram of the electric thermal deicing application of the sensing material of Example 1 of the present invention.
[0018] Figure 7 This is a physical picture of the sensing material of Example 2 of the present invention.
[0019] Figure 8 This is a microstructure diagram of the sensing material of Example 2 of the present invention.
[0020] Fig. 9 This is a diagram of the resistance data caused by the pulse according to the second embodiment of the present invention. DETAILED DESCRIPTION
[0021] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments. Example
[0022] This embodiment provides a method for preparing a microporous TPU / rGO / carbon felt composite material, which specifically includes the following steps: Step 1: Prepare a GO solution with a concentration of 5 mg / mL; select a GO solution with a mass per unit area of 53 g·m −2 The carbon felt was cut into 10 * 10 cm squares, immersed in acetone, and then placed in deionized water, washed several times, and placed in a 60 ° C oven to dry. Then the sample was immersed in a 5 mg / mL GO solution, taken out, and placed in a 60 ° C oven to dry for 1 hour. The above "immersion-drying" steps were repeated 10 times. Subsequently, the prepared sample was placed in HI (hydriodic acid) solution, and the GO on the surface of the carbon felt was in situ reduced to rGO at a temperature of 98 ° C to obtain an rGO / carbon felt composite material; Step 2: Select DMF (dimethylformamide) as the solvent of TPU, mix TPU and DMF in a weight ratio of 1:10 to form a uniform bubble-free TPU solution, and drip the TPU solution into the culture dish (a 1-5mm solution layer is formed at the bottom). Put the sample prepared in step 1 into the culture dish, coat both sides of the sample with TPU solution, and then place it in a room temperature environment to dry. During the drying process, due to the presence of water molecules in the air, TPU quickly separates when it encounters water, causing the surface of TPU to shrink severely, thereby causing the DMF solvent phase to condense, forming thumb-shaped and droplet-shaped uneven micron pores on the surface of the sample, and finally obtaining a micron-porous TPU / rGO / carbon felt composite material such as Figure 1 Its microstructure is shown in Figure 2 , 3 As shown; In an application example of the microporous TPU / rGO / carbon felt composite material prepared in this embodiment, the composite material is connected to a resistance tester to record the real-time resistance signal change caused by the pulse, obtain the corresponding resistance change curve, and organize the data to draw a graph, as shown in FIG. Figure 4 The composite material was attached to the wrist of a female subject at the cun, guan and cun positions to monitor the pulse signals at the three positions. Figure 4 In the data on the left, it is observed that the subject's pulse amplitude is largest at the Guan position and smallest at the Chi position. Figure 4 The right picture shows that the wristband is buckled into different holes (hole-to-hole distance: 8mm) to achieve pressure from low, medium to high, to imitate floating, medium and sinking in traditional Chinese medicine.
[0023] In an application example of the microporous TPU / rGO / carbon felt composite material prepared in this example, the composite material is connected to an electromagnetic shielding instrument, and the electromagnetic shielding signal at a frequency of 500-1500 MHz is recorded, and the data is organized and plotted. Figure 5 shown. Figure 5In the figure, a, b, and c represent the electromagnetic shielding signals of the composite material in one-layer (0.31 mm), two-layer (0.62 mm), and three-layer (0.91 mm) structures, respectively.
[0024] In an application example of the microporous TPU / rGO / carbon felt composite material prepared in this embodiment, the composite material is connected to a DC power supply instrument, and the application in the field of electric heating deicing is recorded, and the data is organized and plotted, as shown in FIG. Figure 6 An ice cube was placed on the composite material, and the melting of the ice cube and its infrared thermal imaging were recorded over time under a voltage of 6V. It can be observed that at 400s, only a small piece of ice cube remained, and at 800s, it was completely melted. Example
[0025] This embodiment provides a method for preparing a microporous TPU / rGO / carbon felt composite material, which specifically includes the following steps: Step 1: Prepare a GO solution with a concentration of 5 mg / mL; select a GO solution with a mass per unit area of 53 g·m −2 The carbon felt was cut into 10 * 10 cm squares, immersed in acetone, and then placed in deionized water, washed several times, and placed in a 60 ° C oven to dry. Then the sample was immersed in a 5 mg / mL GO solution, taken out, and placed in a 60 ° C oven to dry for 1 hour. The above "immersion-drying" steps were repeated 10 times. Subsequently, the prepared sample was placed in HI (hydriodic acid) solution, and the GO on the surface of the carbon felt was in situ reduced to rGO at a temperature of 98 ° C to obtain an rGO / carbon felt composite material; Step 2: Select DMF (dimethylformamide) as the solvent of TPU, mix TPU and DMF in a weight ratio of 1:5 to form a uniform bubble-free TPU solution, and drip the TPU solution into the culture dish (a 1-5mm solution layer is formed at the bottom). Place the sample prepared in step 1 into the culture dish, coat both sides of the sample with TPU solution, and then place it in a room temperature environment to dry. During the drying process, due to the presence of water molecules in the air, TPU quickly separates when it encounters water, causing the surface of TPU to shrink severely, thereby causing the DMF solvent phase to condense, forming thumb-shaped and droplet-shaped uneven micron pores on the surface of the sample, and finally obtaining a micron-porous TPU / rGO / carbon felt composite material such as Figure 7 Its microstructure is shown in Figure 8 As shown; In an application example of the microporous TPU / rGO / carbon felt composite material prepared in this embodiment, the composite material is connected to a resistance tester to record the real-time resistance signal change caused by the pulse, obtain the corresponding resistance change curve, and organize the data to draw a graph, as shown in FIG. Fig. 9The composite material is attached to the pulse of the subject's wrist to record the tiny signal changes caused by the pulse.
[0026] In an application example of the microporous TPU / rGO / carbon felt composite material prepared in this embodiment, the composite material is connected to an electromagnetic shielding instrument, and the electromagnetic shielding signal at a frequency of 500-1500 MHz is recorded. The obtained data is sorted and plotted. Figure 5 shown.
[0027] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, material or apparatus including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, material or apparatus.
[0028] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a microporous TPU / rGO / carbon felt composite material, characterized in that: The steps include: Step 1, preparation of rGO / carbon felt: carbon felt is selected as a substrate, and the substrate is placed in a prepared GO solution for multiple immersion and drying after pretreatment, and then placed in a HI solution to in-situ reduce the GO on the surface of the substrate to rGO, thereby obtaining an rGO / carbon felt composite material; Step 2, preparation of microporous TPU / rGO / carbon felt: prepare a uniform bubble-free TPU solution and place it in a culture dish; place the rGO / carbon felt composite material obtained in step 1 in a culture dish, coat both sides with TPU solution, and then place it in a room temperature environment to dry, to obtain a microporous TPU / rGO / carbon felt with thumb-shaped and droplet-shaped uneven surfaces.
2. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The mass per unit area of the carbon felt is 53 g·m −2 .
3. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The carbon felt was pretreated as follows: cutting it into 10*10 cm squares, immersing it in acetone, and then placing it in deionized water, washing it several times, and placing it in a 60° C. oven to dry it.
4. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The concentration of the GO solution is 5 mg / mL, and the drying condition is: the substrate immersed in the GO solution is placed in an oven at 60° C. for 1 hour.
5. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The steps of immersing the substrate in the GO solution and drying the substrate were repeated 10 times.
6. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The temperature at which the substrate is reduced in the HI solution is 98°C.
7. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: DMF was selected as the solvent of TPU, and TPU and DMF were mixed in a weight ratio of 1:5-1:10 to form a uniform TPU solution without bubbles.
8. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: In step 2, the TPU solution is added to the culture dish by dripping and forms a solution layer of 1-5 mm at the bottom of the culture dish.
9. The method for preparing a microporous TPU / rGO / carbon felt composite material according to claim 1, characterized in that: The particle size range of the micropores formed on the micropore TPU / rGO / carbon felt can be controlled to be 8-50 μm by adjusting the mass ratio of TPU to DMF.
10. An application of a microporous TPU / rGO / carbon felt composite material prepared by the method according to any one of claims 1 to 9, characterized in that: include: Connecting the microporous TPU / rGO / carbon felt composite material to a resistance tester to record a real-time resistance signal caused by pulse; Connecting the microporous TPU / rGO / carbon felt composite material to an electromagnetic shielding instrument to record electromagnetic shielding signals at a frequency of 500-1500 MHz; The microporous TPU / rGO / carbon felt composite material is connected to a direct current power supply instrument to record the electric thermal deicing data.
